Exploring how preschool teachers can secure the evolution of day care institution's culture for applying Risky Play and development for children's personal-, motor- and social skills - Anne Bahrenscheer; Mathilde Sederberg (European Teacher Education Network, 2019)
Risky play is defined as, 'An exciting and challenging game that involves uncertainty and the risk of physical injury.' These are activities where children balance on the verge of losing control. The play is exciting precisely because there is a risk and fear of the unknown. In order to create such possibilities, preschool Teacher need to create frameworks that both allow and contain opportunities for risky play. The research project shows, through interviews with preschool Teacher, that risky play has the potential to help individuals think about play in a different and challenging way. Risky play seems to enhance motor development, initiative, social and personal development as well as wellbeing in interactions between children.